International Trade Secretariats - Dale, Leon (Relations industrielles / Industrial Relations, 1967)
In this article, the author explains the formation and development of International Trade Secretariats (ITS). There was strong pressure to merge international labor organizations into ITS encompassing an industry. Moreover, ITS originally based on individual crafts or trades were gradually replaced by a new type of « industrial » ITS composed of sometimes heterogenous groups of workers.